Broadband 1 × 3 Couplers With Variable Splitting Ratio Using Cascaded Step-Size MMI - Ye Tian; Jifang Qiu; Mingbin Yu; Zhuili Huang; Yingying Qiao; Zhenli Dong; Jian Wu (IEEE Photonics Journal, 2018)
In this paper, we propose and fabricated a novel scheme of SOI-based 1 × 3 coupler with variable splitting ratio. The coupler consists of two cascaded MMI with different sizes, and a wide range of splitting ratios from 1:0.1:1 to 1:18:1 can be achieved by modifying the size of the first-step MMI. Using the structure of cascaded step-size MMI, this kind of device has a compact footprint of below 15 μm × 15 μm and simple fabrication process. Meanwhile, the simulation analyses prove that the proposed couplers have a large operation bandwidth above 60 nm and be robust to the fabrication errors. Couplers with several splitting ratios were fabricated and well measured. Based on the measurement results, the splitting ratios of fabricated couplers from 1:0.67:1 to 1:18:1 can be achieved, and stable performance with the transmission efficiencies above 80% can be maintained over 50 nm wavelength range, which is the largest operation bandwidth to the best of our knowledge.